2020
DOI: 10.1002/cncr.32710
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnosis social support, social integration, living status, and colorectal cancer mortality in postmenopausal women from the women's health initiative

Abstract: Background We evaluated associations between perceived social support, social integration, living alone, and colorectal cancer (CRC) outcomes in postmenopausal women. Methods The study included 1431 women from the Women's Health Initiative who were diagnosed from 1993 through 2017 with stage I through IV CRC and who responded to the Medical Outcomes Study Social Support survey before their CRC diagnosis. We used proportional hazards regression to evaluate associations of social support (tertiles) and types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Social support is regarded as a complex construct that has long been suggested to have direct and ameliorating effects on patients' well‐being and emotional adjustment to cancer (Kroenke et al, 2020 ). Williams et al ( 2019 ) found that 67% of 1460 adult cancer patients reported the need for social support, half reported a need for emotional support and 47% expressed the need for physical support.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is regarded as a complex construct that has long been suggested to have direct and ameliorating effects on patients' well‐being and emotional adjustment to cancer (Kroenke et al, 2020 ). Williams et al ( 2019 ) found that 67% of 1460 adult cancer patients reported the need for social support, half reported a need for emotional support and 47% expressed the need for physical support.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to demonstrate that being single, divorced, or widowed is a risk factor associated with primary site-labeled conjunctival and corneal cancer incidence. Prior studies have primarily only examined the relationship between marital status and other forms of cancer including colorectal cancer [ 22 ], neuroendocrine tumors [ 23 ], and gastric adenocarcinoma [ 24 ] in retrospective [ 25 ] analyses or in prospective analyses [ 26 ]. While several studies have assessed the relationship between marital status and patient prognosis, conclusions have varied significantly among studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increased CRC survival among those who are married, have a life partner, or have other forms of high social support is likely attributable to psychosocial factors, including the availability of emotional support, assistance in monitoring health status, and aid in coping with treatment and shaping preventive health behaviors. [46][47][48] Moreover, individuals with established support systems often experience reduced cortisol levels associated with chronic psychological stress, thereby reducing various inflammatory markers that may provide the opportunity for precancerous cells to grow and flourish. 32,49,50 Although social support has a positive impact on health and health-promoting behaviors, more interventional research is warranted to focus on increasing the survival benefit associated with EOCRC for single or never-married individuals, and for patients with poor social relationships.…”
Section: Discussionmentioning
confidence: 99%